2011
DOI: 10.1016/j.jacc.2011.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Patch Occlusion of the Left Atrial Appendage Using Surgical Adhesives in High-Risk Patients With Atrial Fibrillation

Abstract: Occlusion of the LAA by the TP is feasible and effective in most patients with atrial fibrillation at high risk for embolic stroke. Angiography before placement probably affects patch adhesion and is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…49 Other devices, currently in early animal or human trials, have been developed by, Occlutech, Gore, and Lifetech. The feasibility of the mentioned Lariat non-surgical combined endocardial/epicardial suture ligation of the LAA was first demonstrated in animals by Lee et al in 2010, 46 then in humans by Bartus et al 47 in 2011, and subsequently evaluated in clinical routine.…”
Section: Catheter-based Left Atrial Appendage Occlusionmentioning
confidence: 99%
“…49 Other devices, currently in early animal or human trials, have been developed by, Occlutech, Gore, and Lifetech. The feasibility of the mentioned Lariat non-surgical combined endocardial/epicardial suture ligation of the LAA was first demonstrated in animals by Lee et al in 2010, 46 then in humans by Bartus et al 47 in 2011, and subsequently evaluated in clinical routine.…”
Section: Catheter-based Left Atrial Appendage Occlusionmentioning
confidence: 99%
“…However, randomized data are not available, and a randomized clinical trial was designed but could not be conducted due to failure to obtain the investigational device exemption from the FDA (45). A percutaneously delivered transcatheter patch utilizing surgical adhesives was effective in atrial appendage exclusion, but further studies are not available (46). An animal study has demonstrated feasibility of appendage exclusion with the LAmbre device (47).…”
Section: Future Directions In Appendage Exclusionmentioning
confidence: 99%
“…Concerns about endocardial metal devices have driven the investigation of other non-metal device occluders and an epicardial LAA exclusion approach. The SIDERIS transcatheter patch, a frameless balloon-deliverable device tailored from polyurethane foam, in conjunction with surgical adhesives was shown to be safe and feasible for endocardial LAA occlusion in a small study [16]. The Place procedure with the Lariat suture delivery device (Sentre Heart, CA, USA), applied epicardially via a standard percutaneous pericardial access and directed toward a target magnet wire placed in the LAA via a transseptal approach, demonstrated promising initial data among 13 patients, particularly in the sense of complete LAA occlusion, without leaving intracardiac material behind [19].…”
Section: Drawbacks Of Current Generation Devices and Directions For Impmentioning
confidence: 99%
“…ACP and the WATCHMAN device will have to complete their ongoing US pivotal (ACP) or complementary (WATCHMAN) trials before they can achieve full US FDA approval. Currently, a number of additional transcatheter devices are at different stages of clinical evaluation, for example SIDERIS transcatheter patch (Custom Medical Devices, Athens, Greece) [16], WaveCrest device (Coherex Medical, UT, USA) and Figulla device (Occlutech, Helsingborg, Sweden).…”
Section: History Of Transcatheter Laa Occlusion Proceduresmentioning
confidence: 99%